Research on forklift system / Mohd Khairul Adha Rosli and Mohd. Fairuz Farhan Jamaluddin - Rosli, Mohd Khairul Adha; Jamaluddin, Mohd. Fairuz Farhan (Faculty of Mechanical Engineering, 2002)
A forklift truck is a kind of machine that is used for moving, stacking and unstacking goods carried on wooden pallets or platforms that can be scooped up on the lifting fork. Forklift trucks can be seen in warehouses, factories, hypermarket, airports and seaport. Most of the lifting machines or devices are driven by electric motor. Some machines such as stackers and forklift are commonly powered by diesel engines or petrol engines or low-pressure gas engines. The same power source or unit drives hydraulic mechanisms or pulleys and chains that raise and lower die forks that carry the loads. In addition, some kind of lifting machines such as forklifts may have tilt specialties to make a safer loads loading or being moved. Some of the lifting devices have telescopic masts, which can extend upwards to allow the forks to stack loads up to 5 meter (16ft) above die ground. The carrying capacities vary from five tones with small machines to 50 tonnes or more. Besides that, a heavy weight at the rear of die lifting machines acts to counterbalance the load to preventing from tipping forward. There are many principles of lifting. They may be in the forms of pulley and chains system, pulleys and screws system, hoist and cranes systems, hydraulic mechanism and elevating system. In our research and project, we have decided to choose the winding lever method of lifting system. The method used the screw jack system that turns to raise or lower the fork vertically. One turns is equal to the pitch of the screw’s thread. With a fine pitch, small effort can lift a very heavy load.